Interferência de plantas daninhas na cultura do sorgo sacarino - Silva, Cézar da (2014)
The sweet sorghum crop stands out in the national scenario as an interesting alternative to ethanol production in the inter-crop period of sugar cane. Among the crop treating necessary for the best development of the crop, the weed management deserves attention. The degree of weed interference on the crop depends on factors connected to the weed community (specific composition, density, distribution), to the crop (species, cultivate, spacing and planting densities) and to the season extension of coexistence, and it can be changed by the conditions of soil, climate and management. Therefore, this work had as objective the composition of weed community and evaluate the weed interference periods on the sweet sorghum crop. The experiment was installed under field conditions at Agrossilvipastoril Embrapa, Sinop, MT. The experimental design was randomized block with three replications. The treatments consisted of two periods: control and weeds coexistence at different crop physiological stages: 0-V3, 0-V5, 0-V7, 0-V9 e 0-V11 and two more witnesses, one constantly clean and other in coexistence with weeds during the crop cycle. In the phytosociological survey of weed community were found 15 species inserted in 9 botanical families. The weed species dominant in the experimental field were: Commelina benghalensis, Panicum maximum, Eleusine indica, Digitaria insularis and Cyperus esculentus. At the end of Commelina benghalensis and Panicum maximum crop cycle were the two species of greater relative importance in the area. The weed density decreased and dry matter accumulation increased linearly over time, respectively. It was found that the coexistence of the crop with the weed community not affected the º Brix, however, occasioned decreased linear in the culms diameter and plant height sweet sorghum. Accepting losses of 5% in culms productivity, it was observed that the critical time of weed removal, the critical weed-free period and the critical period of weed control corresponded to phenological stage: V11, V3 end V3 to V11, respectively. The lack of weed control throughout crop cycle decreased culms yield in 51, 22%.